Constitutive over-expression of rice chymotrypsin protease inhibitor gene OCPI2 results in enhanced growth, salinity and osmotic stress tolerance of the transgenic Arabidopsis plants - Tiwari, Lalit Dev (Plant physiology and biochemistry : PPB, 2015)
Copyright © 2015 Elsevier Masson SAS. All rights reserved.